Tracing the historic roots of generalized trust - Benjamin Kalischer Wellander; Tino Sanandaji (Essays in Economic & Business History (EEBH), 2020)
This paper discusses the problem of empirically measuring past trust. Today, the share of the population who generally trusts others ranges from 60-70 percent in Scandinavian countries to as low as 3-4 percent in countries like Colombia and the Philippines. The reasons why certain countries have developed higher trust than others require an understanding of when trust emerged; for instance, whether the high rates of trust in Scandinavia preceded or followed the welfare state. The key problem in disentangling the historic roots of trust is that systematic measurements do not go back far enough. Trust was first systematically measured in 1942 in the United States and 1948 in Germany. The lack of older data has led scholars to develop other methods to indirectly trace historic roots of contemporary trust. They suggest that its roots are deeper than previously thought.
Keywords: 330